The world atlas of rivers, estuaries, and deltas - Best, Jim (Princeton : Princeton University Press, 2024)
From the Congo and the Mekong to the Seine and the Mississippi, Earth's rivers carve through landscapes before coursing into the world's oceans through estuaries and deltas. Their inexorable flow carries sediment and more, acting as lifeblood for a variety of ecosystems and communities. More than any other surface feature of Earth, rivers, estuaries, and deltas are vitally important to our economic and social well-being, and our management of them often sits at the sharp edge of today's most pressing environmental challenges. The World Atlas of Rivers, Estuaries, and Deltas takes readers on an unforgettable tour of these dynamic bodies of water, explaining how they function at each stage of their flow. Combining maps and graphics with informative essays and beautiful photos, this invaluable reference book will give you a new appreciation for the power that rivers, estuaries, and deltas wield. Features a wealth of colour photos, maps, and infographics. Brings together invaluable perspectives from leading experts. Describes the rich biodiversity associated with the world's rivers, estuaries, and deltas. Explains how rivers, estuaries, and deltas work, from river networks to deltaic floodplains, and sheds light on the erosion, movement, and deposition of sediment. Describes the anatomy of rivers, estuaries, and deltas, from channel geometry and river planforms to estuarine shape and delta morphology. Examines the ecology and ecosystems of rivers, estuaries, and deltas and how humans interact with these environments. Additional topics include damming, climate change, water use, pollution, resource management, and planetary health, as well as future perspectives on these vital landscapes.
Includes bibliographical references (pages 388-389) and index.
Keywords: Rivers; Estuaries; Deltas; Estuaires; Deltas; estuaries; deltas; Geography; Nature & the natural world: general interest; The Earth: natural history: general interest; Limnology; Science